Control & Anti-Corruption Measures in the private sector : the case of a listed company on the Stock Exchange of Thailand - Pakonnimiddee, Noppadon (Journal of Thai Ombudsman, 2026)
This article analyzes the gap between the documentary formulation of anti-corruption policies and their practical enforcement, and examines the limitations of corporate governance mechanisms in controlling, monitoring, and regulating the exercise of authority by board members and senior executives—factors that significantly impact the effectiveness of fraud prevention in listed companies. The findings reveal that although most listed companies adopt anti-corruption policies and corporate governance measures conforming to international standards, the existence of such policies alone proves insufficient to effectively prevent or deter fraudulent conduct. This deficiency is attributable to constraints in enforcement mechanisms, audit oversight procedures, and the accountability of board members and executives in cases of organizational fraud. Consequently, instances of misconduct by board members and senior management continue to occur, causing substantial damage to shareholders, investors, and public interest. The author concludes that fraud prevention and suppression in the private sector cannot rely exclusively on corporate-level anti-corruption policies. Rather, legal mechanisms must be enacted to reinforce and enhance enforcement effectiveness. Specifically, anti-corruption principles should be integrated into the reform and development of public limited company legislation and securities laws, aimed at elevating the liability standards for board members and executives and substantially improving fraud prevention and control mechanisms within the private sector.